2007
DOI: 10.1096/fj.06-8061com
|View full text |Cite
|
Sign up to set email alerts
|

Dipyrone elicits substantial inhibition of peripheral cyclooxygenases in humans: new insights into the pharmacology of an old analgesic

Abstract: Dipyrone (INN, metamizol) is a common analgesic used worldwide. Its widespread prescription or over-the-counter use in many countries (e.g., Brazil, Israel, Mexico, Russia, Spain) requires insight into its mode of action. This study therefore addressed the impact of its metabolites 4-methyl-amino-antipyrine (MAA) and 4-amino-antipyrine (AA) on peripheral cyclooxygenases (COX). Pharmacokinetics of metabolites and ex vivo COX inhibition were assessed in five volunteers receiving dipyrone at single oral doses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
3
18

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 52 publications
0
89
3
18
Order By: Relevance
“…For a long time, metamizole was considered to be a non-selective COX-1 and COX-2 inhibitor (Hinz et al 2007, Pierre et al 2007, Rogosch et al 2012. The mechanism involved in its analgesic effect is complex (Fig.…”
Section: The Mechanism Of the Drug's Activity And Pharmacological Effmentioning
confidence: 99%
See 2 more Smart Citations
“…For a long time, metamizole was considered to be a non-selective COX-1 and COX-2 inhibitor (Hinz et al 2007, Pierre et al 2007, Rogosch et al 2012. The mechanism involved in its analgesic effect is complex (Fig.…”
Section: The Mechanism Of the Drug's Activity And Pharmacological Effmentioning
confidence: 99%
“…Unquestionably, the drug inhibits COX-3 more strongly (Chandrasekharan et al 2002). Although is has been shown that metamizole inhibits both COX-1 and COX-2 (Campos et al 1999, Hinz et al 2007, Pierre et al 2007, it is uncertain whether the effect is clinically significant because we lack a substantial body of evidence proving that this medication can cause a significant anti-inflammatory effect.…”
Section: The Mechanism Of the Drug's Activity And Pharmacological Effmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our results, it might be assumed that acetaminophen has some effect on the inflammatory response, as the correlations of cumulative NSAID days with IL-6 and CRP were weaker without acetaminophen. Another NSAID drug that was included in the analysis was dipyrone, which has pronounced analgesic and antipyretic effects, but weak anti-inflammatory effects as well [23]. Although its mechanism of action is not entirely clear, it elicits substantial inhibition of COX in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is useful for the treatment of cancer pain and migraine as well as fever refractory to other treatments. 1 Dipyrone is a pro-drug that undergoes non-enzymatic hydrolysis in the stomach to form 4-methylamino-antipyrine . This active metabolite is rapidly and almost completely absorbed.…”
mentioning
confidence: 99%